“HAYRATUL-ABROR” DOSTONINING POETIK TUZILISHI VA KOMPOZITSION XUSUSIYATLARI - Karimov, O. (SCIENCE and SOCIETY, 2022)
The article presents a unique plot, poetic structure and compositional features, as well as a chain of compositions that distinguishes “Hayrat ul-abror” from the other “Khamsa’s” poems.